An Analysis of errors committed by fourth year high school students of San Beda College - Luna, Jacklyn Kate A.; Arcellana, Lydia R. (Quezon City College of Arts and Letters, University of the Philippines Diliman, 2004)
This paper investigates the most common types of grammatical errors committed by fourth year high school students of San Beda College in their learning of English as a second language. It aims to find out the causes of these grammatical and the faulty learning strategies employed by these second-language learners in applying the rules of the target language. This paper also determines the implications of these grammatical errors to English language teaching and learning. And with those concerns at hand, this research intends to discover possible instructional materials in language teaching and learning and establish effective remedial strategies in language teaching and learning that can improve the learning of these students. Error analysis is the method used as the theoretical framework because unlike the contrastive analysis which views errors as hindrances, error analysis regards these errors as positive aids in the discovery of strategies employed by learners in the course of learning their second language. After collecting the data for this research, each informal theme was carefully examined and each error found was correspondingly entered in a tally sheet. After finally tabulating the results, the researcher analyzed these errors in the light of their possible causes. Results showed that the errors verb-tense disagreement, addition of unnecessary word/ omission of necessary word, wrong spelling were the most predominant committed by second language learners of English. In tracing the causes of these errors, it was found that the students tend to false concept hypothesize which is the most often faulty. The errors obtained from the English compositions analyzed for this paper proved the assumptions that errors are inevitable and are actually employed in the learning process. The occurrence of incorrect forms of grammatical rules shows that hypotheses about the target language are constantly being formed. The errors analyzed illustrate some patterns showing that the errors committed are systematic and since these patterns are peculiar to the language learners, the students' written compositions represent their own version of the target language and as a result, the learners' errors are systematic. Since most of the students attempt to write in English in order to communicate, their compositions are largely accompanied by deviations from the rules of grammar. Therefore, English teachers should give more attention in teaching grammar to their students in order for them to be able to communicate in the target language using correct grammatical expressions.
Thesis (B.A. in English Studies : Language)--University of the Philippines Diliman
Includes bibliographical references and appendices.